Kinds of Social Protests in Margaret Atwood's The Handmaid’s Tale - Khusna, Siska Nihayatul; Zainullah, Ahmad (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2022)
Abstract Social protest is an expression or action that expresses a complaint, rebuttal, or rejection from the ordinary people against an individual or institution in power. Lofland defines social protest as an expression or complaint of ordinary people to the government because of a political, cultural, or economic social crisis. In this study, the researcher aims to analyze social protest in Margaret Atwood's The Handmaid’s Tale to understand the types of social protest in depth. The research method used in this study is literary criticism. The researcher uses John Lofland's theory of social protest in analyzing and interpreting the novel The Handmaid’s Tale by Margaret Atwood to obtain an overview of the types of social protest. Based on the findings and discussion, there are four types of social protest in Margaret Atwood's novel The Handmaid’s Tale: symbolic social protest, anti- cooperation social protest, intervention social protest, and alternative institutional social protest. Symbolic social protests are linked to issues of sexual slavery, oppression of women, and loss of freedom. Anti-cooperation social protests are related to sexual slavery, oppression of women, and loss of freedom. Interventional social protests are linked to issues of sexual slavery, oppression of women, and loss of freedom. Alternative social institutions protest the loss of freedom. Keywords: Kinds of Social Protests in Margaret Atwood's The Handmaid’s Tale